PIDANA MATI SARANA PENCEGAHAN TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA - Barhamudin, Barhamudin (Solusi, 2018)
The purpose of this research is: To know and analyze the ratio of the punishment of capital punishment in the positive law arrangement in Indonesia is not contradictory to human rights. To know and analyze capital punishment from the aspect of crime prevention; This study is a normative legal research that focuses on explanation or explanation of the application of capital punishment to the perpetrators of narcotics abuse in the perspective of human rights. This research is normative research using approach of legislation, conceptual approach and approach of analysis. The death penalty against the perpetrators of crimes committed in Indonesia does not affect or reduce crime, according to the authors precisely because of the very low level of the number of judges in Indonesia who dropped the death penalty and the execution of the execution long enough to continue the rampant perpetrators of crimes in general, especially the Bandar and the current narcotics dealer. If the imposition of capital punishment on the dealers and narcotics dealers reaches twenty percent (20%) per cent alone it is certain to decrease and provide a deterrent effect for prospective dealers and dealers or residuals. The death penalty is the most effective suggestion that governments can use to combat crime. The death penalty is intended to reciprocate the mistake and secure the public from the dealers and narcotics as specified in the narcotics law while the Action intends to secure and maintain the objectives applied to addicts and victims. So criminal and action, both aims to prepare to return the convicted into the life of the community. The basis of each of the penalties is the grave suffering according to the severity of the acts committed by the convicted person. But to what extent the severity of the crime and the severity of the acts committed by the convict can be measured, determined by what is useful to the public.